Migraine therapeutics differentially modulate the CGRP pathway. (April 2021) - Bhakta, Minoti; Vuong, Trang; Taura, Tetsuya; Wilson, David S; Stratton, Jennifer R; Mackenzie, Kimberly D
Background: The clinical efficacy of migraine therapeutic agents directed towards the calcitonin-gene related peptide (CGRP) pathway has confirmed the key role of this axis in migraine pathogenesis. Three antibodies against CGRP – fremanezumab, galcanezumab and eptinezumab – and one antibody against the CGRP receptor, erenumab, are clinically approved therapeutics for the prevention of migraine. In addition, two small molecule CGRP receptor antagonists, ubrogepant and rimegepant, are approved for acute migraine treatment. Targeting either the CGRP ligand or receptor is efficacious for migraine treatment; however, a comparison of the mechanism of action of these therapeutic agents is lacking in the literature. Methods: To gain insights into the potential differences between these CGRP pathway therapeutics, we compared the effect of a CGRP ligand antibody (fremanezumab), a CGRP receptor antibody (erenumab) and a CGRP receptor small molecule antagonist (telcagepant) using a combination of binding, functional and imaging assays. Results: Erenumab and telcagepant antagonized CGRP, adrenomedullin and intermedin cAMP signaling at the canonical human CGRP receptor. In contrast, fremanezumab only antagonized CGRP-induced cAMP signaling at the human CGRP receptor. In addition, erenumab, but not fremanezumab, bound and internalized at the canonical human CGRP receptor. Interestingly, erenumab also bound and internalized at the human AMY1 receptor, a CGRP receptor family member. Both erenumab and telcagepant antagonized amylin-induced cAMP signaling at the AMY1 receptor while fremanezumab did not affect amylin responses. Conclusion: The therapeutic effect of agents targeting the CGRP ligand versus receptor for migraine prevention (antibodies) or acute treatment (gepants) may involve distinct mechanisms of action. These findings suggest that differing mechanisms could affect efficacy, safety, and/or tolerability in migraine patients.